2003
DOI: 10.1186/1476-7961-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Mite and cockroach proteases activate p44/p42 MAP kinases in human lung epithelial cells

Abstract: Background: The mechanisms underlying epithelial cell activation by indoor inhaled antigens are poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These cells produce many cytokines in response to dust mite molecules. These studies have shown that molecules in house dust mite extracts or specific allergens stimulate lung epithelial cells to secrete cytokines, including IL-6, IL-8, GM-CSF and eotaxin (CCL11) [29,30,31,32,33,34,35,36,37]. These same cytokines and chemokines are released by cultured fibroblasts and keratinocytes and by the cells in HSEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells produce many cytokines in response to dust mite molecules. These studies have shown that molecules in house dust mite extracts or specific allergens stimulate lung epithelial cells to secrete cytokines, including IL-6, IL-8, GM-CSF and eotaxin (CCL11) [29,30,31,32,33,34,35,36,37]. These same cytokines and chemokines are released by cultured fibroblasts and keratinocytes and by the cells in HSEs.…”
Section: Discussionmentioning
confidence: 99%
“…The different responses by pure cultured cells and skin equivalent tissue illustrate the danger of using cultured cells to determine the overall effect of dust mites on cells that are involved in allergic and asthmatic reactions. Many studies have stimulated lung epithelial cells in culture with house dust mite extract or recombinant house dust mite allergen [19,29,30,31,32,33,34,35]. These cells produce many cytokines in response to dust mite molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kuderer et al [11] reported that mite protease leads to the activation of ERK, which results in the expression of the IL-8 gene in human lung epithelial cells. We extended their study by examining the transduction pathways induced by HDM stimuli for IL-8 production in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Stacey et al [10] reported that nuclear factor ĸB activation plays a dominant role in Der p 1-induced chemokine production. Additionally, Kuderer et al [11] showed that extracellular signal-regulated kinase (ERK) may play an important role in D. farinae -induced IL-8 production. Thus, we examined the roles of various signaling molecules activated by D. farinae .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, PAR-2 is cleaved and activated by serine proteases, such as trypsin [18,19] and the house dust mite allergens Der p 3 and Der p 9 [20]. On the other hand, in a human epithelial cell line stimulated with German cockroach extract, the aspartate protease inhibitor pepstatin A and the cysteine protease inhibitor E64, inhibited phospho-p44 MAP kinase levels [44], suggesting a role for cysteine proteases or aspartate proteases. Our study of eosinophils [22] supports and extends the findings of earlier studies that demonstrated German cockroach extract activation of PAR-2 in human airway epithelial cells [15,45], mouse lung fibroblasts [46], and human keratinocytes [40].…”
Section: Epithelial Cellsmentioning
confidence: 99%